The great austerity war: What caused the deficit crisis and who should pay to fix it? - James Crotty (University of Massachusetts, Department of Economics, 2011)
Rapidly rising deficits at both the federal and state and local government levels, along with longterm financing problems in the Social Security and Medicare programs, have triggered a onesided austerity-focused class war in the US. Similar class conflicts have broken out around the globe. A coalition of the richest and most economically powerful segments of society and conservative politicians who represent their interests has demanded that deficits be eliminated by public-sector austerity - severe cuts at all levels of government in spending that either supports the poor and the middle class or funds crucial public investment. These demands constitute a deliberate attempt to destroy the New Deal project, begun in the 1930s, whose goal was to subject capitalism to democratic control. The right-wing coalition seeks to replace that project with a modernized version of the 'free-market' capitalism of the 1920s. In this paper I argue that our deficit crisis is the result of a shift from the New-Deal-based economic model of the early post-war period to today's neoliberal, free-market model, a shift initiated under Ronald Reagan and continued under the presidents who succeeded him. The new model has generated slow growth, rising inequality and rising deficits. Rising deficits in turn created demands for austerity. After tracing the long-term evolution of our current deficit crisis, I show that this crisis can be resolved by raising taxes on upper-income households and large corporations, cutting war spending, and adopting a Canadian or European style health care system. There is no need to accept austerity. Calls for austerity should be seen as what they are - an attack by the rich and powerful against the basic interests of the American people.
Keywords: E60; E62; H60; 330; deficit crisis; fiscal crisis; austerity; Social Security crisis; health care crisis.